Introduction of Torbangun Leaves as the Best Traditional Lactagogue and its Processing Innovations in Antasan Senor Village, Banjar Regency, South Kalimantan, Indonesia - Dwi Andrestian, Meilla; Dewi, Zulfiana; Mas'odah, Siti; Hapisah, Hapisah; Noraini, Noraini (Engagement: Jurnal Pengabdian Kepada Masyarakat, 2024)
Torbangun leaves have been used by the Batak people in North Sumatra and have been scientifically proven to be the most effective lactagogue. Therefore, it is necessary to introduce the benefits of Torbangun leaves to improve welfare, and breastfeeding coverage in the working area of the East Martapura Health Center, Banjar Regency, South Kalimantan Province, especially in Antasan Senor Village as a Village Assisted by the Banjarmasin Health Polytechnic. The purpose of the activity is to educate Integrated Service Post (Posyandu) cadre members and pregnant women in the management of breastfeeding, introduction of Torbangun plants and development of processed Torbangun leaves. The methods implemented in this activity are education and practice. The target group is seven Posyandu cadres and three pregnant women. Although statistically insignificant, the activity has succeeded in improving the knowledge, attitudes, and behavior of participants in the management of breastfeeding, the ability to cultivate Torbangun plants, and innovation of Torbangun leaves products as lactagogue. This activity has provided theory and practice to encourage awareness of breastfeeding, cultivation of Torbangun plants, and development of processed products of Torbangun leaves.